Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: DS: Richard (m08q20) [#permalink]
19 Aug 2010, 21:15

1

This post received KUDOS

Richard is 3 years younger than his sister. We just need to know his current age to know his age in 5 years. Lets R be his current age and S be the current age of his sister. S=R+3

1/ S-2=2(R-2)-->S=2R-2 from this we can write 2R-2=R-3-->R=5 sufficient (Richard will be 10) 2/S+2=2R-->S=2R-2 from this we can write 2R-2=R-3-->R=5 sufficient (Richard will be 10)

Re: DS: Richard (m08q20) [#permalink]
22 Aug 2010, 04:32

2

This post received KUDOS

I just put the real numbers:

The difference is 3 years, how old will he be in 5 years? 1. If the difference is 3 years, he was 3 and she was 6. Now he is 5 (2 years later), in 5 years will be 10. Sufficient. 2. If the difference was 5 years instead, she is twice as old as him, means that he is 5 she is 10. He'll be 10 in 5 years. Sufficient.

Re: DS: Richard (m08q20) [#permalink]
02 Feb 2011, 11:21

1

This post received KUDOS

Expert's post

tinki wrote:

sister now : s, richard now: s-3 st 1. 2(s-3-2) = s-2 St 2. s-2=2(s-3)

Could somebody help? whats wrong with my statements and logic? thanks

If Richard is 3 years younger than his sister, how old will Richard be in 5 years?

Given: r=s-3. Question: r+5=s+2=?

(1) Two years ago Richard was twice as young as his sister --> 2*(s-3-2)=s-2 --> s=8 --> r+5=s+2=10. Sufficient. (2) If Richard's sister were born 2 years earlier, she would now be twice as old as Richard --> if Richard's sister were born 2 years earlier she would now be s+2 years old not s-2, so s+2=2(s-3) --> s=8 --> r+5=s+2=10. Sufficient.

Re: DS: Richard (m08q20) [#permalink]
02 Feb 2011, 13:04

Bunuel wrote:

tinki wrote:

sister now : s, richard now: s-3 st 1. 2(s-3-2) = s-2 St 2. s-2=2(s-3)

Could somebody help? whats wrong with my statements and logic? thanks

If Richard is 3 years younger than his sister, how old will Richard be in 5 years?

Given: r=s-3. Question: r+5=s+2=?

(1) Two years ago Richard was twice as young as his sister --> 2*(s-3-2)=s-2 --> s=8 --> r+5=s+2=10. Sufficient. (2) If Richard's sister were born 2 years earlier, she would now be twice as old as Richard --> if Richard's sister were born 2 years earlier she would now be s+2 years old not s-2, so s+2=2(s-3) --> s=8 --> r+5=s+2=10. Sufficient.

Re: DS: Richard (m08q20) [#permalink]
29 Apr 2012, 11:53

Bunuel wrote:

tinki wrote:

sister now : s, richard now: s-3 st 1. 2(s-3-2) = s-2 St 2. s-2=2(s-3)

Could somebody help? whats wrong with my statements and logic? thanks

If Richard is 3 years younger than his sister, how old will Richard be in 5 years?

Given: r=s-3. Question: r+5=s+2=?

(1) Two years ago Richard was twice as young as his sister --> 2*(s-3-2)=s-2 --> s=8 --> r+5=s+2=10. Sufficient. (2) If Richard's sister were born 2 years earlier, she would now be twice as old as Richard --> if Richard's sister were born 2 years earlier she would now be s+2 years old not s-2, so s+2=2(s-3) --> s=8 --> r+5=s+2=10. Sufficient.

Answer: D.

Bunuel,

I have a question about 1) - When we say "Richard is twice as young as his sister" - doesn't it mean that R=2S? I am a bit confused.

Re: DS: Richard (m08q20) [#permalink]
29 Apr 2012, 11:58

1

This post received KUDOS

Expert's post

voodoochild wrote:

Bunuel wrote:

tinki wrote:

sister now : s, richard now: s-3 st 1. 2(s-3-2) = s-2 St 2. s-2=2(s-3)

Could somebody help? whats wrong with my statements and logic? thanks

If Richard is 3 years younger than his sister, how old will Richard be in 5 years?

Given: r=s-3. Question: r+5=s+2=?

(1) Two years ago Richard was twice as young as his sister --> 2*(s-3-2)=s-2 --> s=8 --> r+5=s+2=10. Sufficient. (2) If Richard's sister were born 2 years earlier, she would now be twice as old as Richard --> if Richard's sister were born 2 years earlier she would now be s+2 years old not s-2, so s+2=2(s-3) --> s=8 --> r+5=s+2=10. Sufficient.

Answer: D.

Bunuel,

I have a question about 1) - When we say "Richard is twice as young as his sister" - doesn't it mean that R=2S? I am a bit confused.

Look at this in this way, if Richard is twice as young as his sister, then Richard is less years old, so it cannot be R=2S since in this case R>S. It should be S=2R.

Re: DS: Richard (m08q20) [#permalink]
24 Aug 2012, 07:00

R=age of Rich NOW S=age of his sister NOW

From the promt, we know that R=S+3 R+5=? --> The information we need is: R=?

1) R=S+3 so two years before now... R-2=S+1--> What we would know according to the promt (S+1)/2=S-2 --> what we know from the promt THEREFORE S=5. From here we can figure out what R is. SUFFICIENT.

2) (s+2)+3=2R R=S-3 --> (S+5)/2=S-2--> same info as (1) therefore SUFFICIENT.

Re: DS: Richard (m08q20) [#permalink]
29 Aug 2012, 23:37

I did end up getting D as the answer as well. Since it is a D.S. question I did not proceed to solve for the values. As long as we have two distinct equations with 2 variables then they are solvable.

Statement (i) gives a distinct equation of s-2=2(r-2)

Statement (ii) gives a distinct equation of s+2=2r

Both of these equations can be solved with the given equation that r=s-3.

Hence both statements are sufficient. Thus D. _________________

My attempt to capture my B-School Journey in a Blog : tranquilnomadgmat.blogspot.com

Re: DS: Richard (m08q20) [#permalink]
26 Aug 2013, 17:02

1

This post received KUDOS

Currently Richard's age=R and sister's age=S Given: S-R=3...eqn(1) to find: R+5=?

1) 2(R-2)=S-2 , i.e. 2R-S=2...eqn(2) solving (1) and (2) we get R=5 sufficient 2) S+2=2R, i.e 2R-S=2....same eqn as in statement(1), we get R=5 sufficient

Re: DS: Richard (m08q20) [#permalink]
27 Aug 2013, 14:02

Bunuel wrote:

tinki wrote:

sister now : s, richard now: s-3 st 1. 2(s-3-2) = s-2 St 2. s-2=2(s-3)

Could somebody help? whats wrong with my statements and logic? thanks

If Richard is 3 years younger than his sister, how old will Richard be in 5 years?

Given: r=s-3. Question: r+5=s+2=?

(1) Two years ago Richard was twice as young as his sister --> 2*(s-3-2)=s-2 --> s=8 --> r+5=s+2=10. Sufficient. (2) If Richard's sister were born 2 years earlier, she would now be twice as old as Richard --> if Richard's sister were born 2 years earlier she would now be s+2 years old not s-2, so s+2=2(s-3) --> s=8 --> r+5=s+2=10. Sufficient.

Answer: D.

Can you provide more detail in the steps of statement 1 and 2. I know you're using some shortcuts but I can't seem to follow.

Thanks,

gmatclubot

Re: DS: Richard (m08q20)
[#permalink]
27 Aug 2013, 14:02